Maternal Weight Control Behaviors for Preschoolers Related to Children’s Gender. - Chae, Sun-Mi; Ra, Jin Suk (Journal of Child & Family Studies, 2018)
The purpose of this study was to identify significant factors associated with Korean mothers’ behaviors in controlling their preschool children’s weight and to examine gender differences among the significant associated factors. This study involved a convenience sample of 223 pairs of mothers and their preschool children (114 boys and 109 girls) in South Korea. Maternal desire for their children to lose weight, concern about children being overweight or obese, and interaction between gender and concern about children being overweight or obese were significant factors associated with maternal behaviors to control children’s weight. Regarding the interaction between gender and concern about children being overweight or obese, mothers who were concerned about their daughter being overweight or obese were more likely to control their child’s weight than those who were concerned about their son being overweight or obese. Additionally, mothers with concerns about their daughter being overweight or obese were more likely to conduct weight control behaviors for their child than mothers of girls without such concern. However, among mothers of boys, there was no difference in maternal behaviors to control their child’s weight between those with concern and without concern. Therefore, health care providers should understand gender specific maternal concerns regarding their child’s weight and provide tailored weight control interventions for mother and child pairs considering the child’s gender.